2021
DOI: 10.1099/acmi.0.000212
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae co-infection with SARS-CoV-2: A case report

Abstract: We report co-infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Mycoplasma pneumoniae in a patient with pneumonia in India. Atypical bacterial pathogens causing community-acquired pneumonia may share similar clinical presentations and radiographic features with SARS-CoV-2 making a thorough differential diagnosis essential. The co-infection of SARS-CoV-2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…For one patient in our cohort, the co-infection with SARS-CoV-2 and Mp was fatal. The clinical course of this patient has been reported in a previous publication by our group ( 32 ). Patients with COVID-19 and MPP may have a similar clinical presentation and radiographic features; therefore, all critically ill patients with COVID-19 should be meticulously tested for other atypical pathogens including Mp to ensure adequate treatment.…”
Section: Discussionsupporting
confidence: 57%
“…For one patient in our cohort, the co-infection with SARS-CoV-2 and Mp was fatal. The clinical course of this patient has been reported in a previous publication by our group ( 32 ). Patients with COVID-19 and MPP may have a similar clinical presentation and radiographic features; therefore, all critically ill patients with COVID-19 should be meticulously tested for other atypical pathogens including Mp to ensure adequate treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Coinfection with M. pneumoniae or C. pneumoniae was not identified. However, we previously reported M. pneumoniae coinfection in a patient with SARS-CoV-2 using an in-house PCR ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports from different parts of the world have shown that Mycoplasma pneumoniae co-infections in COVID-19 patients result in disease severity. [42][43][44][45][46][47][48][49] Patients with atypical respiratory pathogens such as Mycoplasma pneumoniae or Chlamydia pneumoniae co-infections have high propensity of developing acute respiratory distress syndrome (ARDS). 43 Both COVID-19 pneumonia and pulmonary pneumonia elicit fever, cough, and shortness of breath, and present similar diagnostic features in chest X-rays and HRCT, because of which they escape logical diagnosis by clinicians.…”
Section: Discussionmentioning
confidence: 99%